Brave - Chmakova, Svetlana, 1979- (New York, NY : Yen Press, 2017)
"In his daydreams, Jensen is the biggest hero that ever was, saving the world and his friends on a daily basis. But his middle school reality is very different--math is hard, getting along with friends is hard...Even finding a partner for the class project is a big problem when you always get picked last. And the pressure's on even more once the school newspaper's dynamic duo, Jenny and Akilah, draw Jensen into the whirlwind of school news, social experiment projects, and behind-the-scenes club drama. Jensen has always played the middle school game one level at a time, but suddenly, someone's cranked up the difficulty setting. Will those daring daydreams of his finally work in his favor, or will he have to find real solutions to his real life problems?"--Provided by publisher.
Library Media Connection starred
Library Media Connection starred, November 2017
5-8
Keywords: Clubs -- Comic books, strips, etc. -- Juvenile fiction; Middle schools -- Comic books, strips, etc. -- Juvenile fiction; Popularity -- Comic books, strips, etc. -- Juvenile fiction; Schools -- Comic books, strips, etc. -- Juvenile fiction; Clubs -- Fiction; Middle schools -- Fiction; Popularity -- Fiction; Schools -- Fiction; Clubs -- Comic books, strips, etc. -- Fiction; Middle schools -- Comic books, strips, etc. -- Fiction; Popularity -- Comic books, strips, etc. -- Fiction; School stories; Graphic novels